Sustainable Campus Through Solid Waste Minimization Strategies (Case study: Universitas Agung Podomoro in Indonesia) - Alifia Intan Safitri; Elsa Try Julita Sembiring; Maria Prihandrijanti (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
A large amount of solid waste (SW) generation becomes inevitable for campus due to its population and variety of activities. Therefore, it is a challenge to develop and implement SW minimization plan to encourage sustainable campus practices. The aim of this study was to develop sustainable strategies to support this plan for Universitas Agung Podomoro (UAP) included evaluating the SW management condition by monitoring the SW generation and surveying the perception and willingness to participate of campus society. The results showed that the SW generation was 52.63 kg/day or 0.08 kg/person/day. The composition consisted of 32.29% biodegradable and 67.71% non-biodegradable. The recycling potential was 61.01% consisted of 22.28% composting and 38.73% recycling. The social survey showed that respondents had positive perceptions about SW minimization. The complete evaluation resulted in the development of strategies to decrease the SW generation rate, increase the recyclable material rate, and increase the participation of campus society.